The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1177/0023830909351220
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Use Leads to Automaticity of Production: Evidence from Repair in Conversation

Abstract: In spontaneous speech, speakers sometimes replace a word they have just produced or started producing by another word. The present study reports that in these replacement repairs, low-frequency replaced words are more likely to be interrupted prior to completion than high-frequency words, providing support to the hypothesis that the production of high-frequency words is more automatic than the production of low-frequency words (Bybee, 2002; Logan, 1982). Frequency appears to have an effect on interruptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 49 publications
10
27
0
Order By: Relevance
“…Kapatsinski (2010) has shown that in lexical repair, more frequent words are less likely to be interrupted prior to repair than less frequent ones; at the same time, it seems reasonable to expect a higher-frequency word to allow for a faster repair than a low-frequency word.…”
Section: Statistical Modellingmentioning
confidence: 99%
“…Kapatsinski (2010) has shown that in lexical repair, more frequent words are less likely to be interrupted prior to repair than less frequent ones; at the same time, it seems reasonable to expect a higher-frequency word to allow for a faster repair than a low-frequency word.…”
Section: Statistical Modellingmentioning
confidence: 99%
“…The interaction between reparandum item completeness and lexical frequency, observed by Kapatsinski (2010) and confirmed by our analysis, complicates the issue: are high-frequency reparandum items typically completed because they are not detected as repairable in inner speech monitoring, or because once their articulation has started, it is difficult to stop even if the 'stop' signal came early? If the latter is the case, this would mean that reparandum item completeness is an unreliable indicator of detection timing at best.…”
Section:  Hypothesis Bmentioning
confidence: 61%
“…For EXPECTATIONS 3 and 4, we have found that linguistic error repairs are significantly different from both appropriateness and factual error repairs in terms of their frequency and offset timing characteristics. The observed differences between factual and linguistic error repairs are particularly notable, given that these have not been consistently distinguished in previous work on repair prosody, including Levelt & Cutler (1983), Kormos (2000 and Kapatsinski (2010).…”
Section: Relationships Between Offset Timing Repair Semantics Frequmentioning
confidence: 63%
See 2 more Smart Citations